Species identification of potential probiotic lactic acid bacteria isolated from Malaysian fermented food based on 16S ribosomal RNA (16S rRNA) and internal transcribed spacer (ITS) sequences - Yaacob Ilyanie,; Nur Huda Faujan,; Md Yasin Ida Muryany, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Taxonomic identification of potential probiotic lactic acid bacteria (LAB) in fermented foods is essential as the microorganisms’ benefits are varied and often strain-specific. Using biochemical and physiological methods alone is inadequate to precisely distinguish each strain. In this study, molecular techniques were employed in the identification of 17 LAB isolated from three Malaysian fermented foods: belacan (BE), bosou (BO), and budu (BUM). The respective sizes of polymerase chain reaction (PCR) products from the isolates were approximately 1500 bp and 750 bp when amplified with the 16S ribosomal RNA (16S rRNA) and internal transcribed spacer (ITS) gene primers. The phylogenetic analysis using both gene sequences revealed that all BE and BO isolates were identified as Lactiplantibacillus plantarum, while all BUM isolates were identified as Lacticaseibacillus paracasei. Both 16S rRNA and ITS genes could disclose the identity of the isolates up to the species level. In summary, the use of the ITS gene in conjunction with the 16S rRNA gene can help with the more effective identification of potential probiotic LAB strains isolated from fermented food.